La producción poética carcelaria argentina: un estatus ambiguo (Estudios) - Guillard, Amandine (2016)
This work seeks to reflect on the status of the poetry written in prisons of the last Argentinean dictatorship between 1976 and 1983. The numerous testimonies of survivors that have emerged in the last years revealed multiple activities developed in prisons in the dictatorship, in particular, the systematic practice of writing poetry in almost every penitentiary in the country. However, this production is not often studied for its literary value, but more for its historic one, as an exclusive product of confinement. First, we will try to understand de rise of this poetry in, and from, the Argentinean and Latin-American cultural context from this period, and second, we will return to think about the status of the authors in prison, and therefore, of their poems.